Analisis Kebutuhan Investasi Sektor Potensial di Kabupaten Buleleng - Devi, Ida Ayu Widya Paramahita; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 12, Desember 2014 (pp. 549-623), 2014)
The purpose of this research is to know the sectors into a potential sector in the Regency of Buleleng and how big the potential sectors for investment needs in the Regency of Buleleng in 2013-2017. The Data used are the provincial GDP and GRDP Buleleng Regency of Bali on the basis of constant prices of 2000. The analysis used in this analysis is the technique of research Location Quotient (LQ) where LQ is the potential sector 1 > and ICOR. The results found that the sectors into a potential sector in the Regency of Buleleng that the agricultural sector with the sub sectors of food crops, crop plantation sector, sub sub sectors of the farm and its results. Second, the mining and quarrying sector with sub sector of the excavation. Lastly, the services sector with the public administration sector, sub sub sector subsector civic and social sub sector of individuals and households. About sub sectors i.e. While the results of this research show the sub sectors that require the most investment, namely sub private sector amounting to Rp. 18.231.131, include sub-sub sectors social development amounting to Rp. 1.277.151,-sub-sub individualized and household sectors amounting to Rp. 17.302.034,-.
Keywords: PDRB; Investasi; Sektor Potensial; Kabupaten Buleleng; ICOR